The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from Austria and Germany. (4th May 2017) - Fülbier, Rolf Uwe; Pelger, Christoph; Kuntner, Evamaria; Bravidor, Marcus
Abstract: Austria and Germany share similar accounting traditions. International harmonization in both countries has mainly focused on group accounting. In contrast, single financial statements give rise to legal and tax consequences and, thus, are still tied to the traditional principles of orderly accounting. Recent regulatory changes confirmed this dual role of accounting in both countries, while moving local accounting rules closer to IFRS, although to different extents. We illustrate how recent regulations in the two countries made reference to IFRS, how IFRS was considered during the law-making process and outline major differences that remain between domestic and international accounting standards.